Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Employee Engagement melalui Kepuasan Kerja - Farah Ghaya Alya; Riedel Paulus Jacobis (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Employee engagement is an important factor in improving employee performance and organizational commitment. This study aims to examine the influence of work environment and work motivation on employee engagement through job satisfaction as a mediating variable at PT INKA Multi Solusi. This research employed a quantitative approach using purposive sampling technique involving 114 employees from the Human Resources & Risk Management, Finance, Technology, and Logistics divisions. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that the work environment and work motivation do not have a significant effect on employee engagement. However, job satisfaction has a positive and significant effect on employee engagement. In addition, work environment and work motivation significantly influence job satisfaction. The mediation analysis shows that job satisfaction does not mediate the relationship between work environment and employee engagement. Conversely, job satisfaction successfully mediates the relationship between work motivation and employee engagement. These findings imply that improving employee job satisfaction is essential in strengthening employee engagement within the company.